Rising rates of caesarean section: an indicator of defensive medicine practiced by obstetricians - Bhatara, Urvashi; ., Padmasri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Defensive medicine can be in the form of excessive tests, procedures, surgeries, or visits by the doctors to primarily reduce their exposure to legal liabilities. It also includes avoidance of high risk patients or procedures. Medical profession has been included under consumer protection act which has led in developing hostile environment for medical practitioners. This has led to increase in defensive medicine. In obstetrics and gynaecology incorporation of defensive medicine can be scrutinized by observing trends in caesarean section. Methods: It is a retrospective study carried out for 1 year from January 2015 to December 2015. All patients in whom caesarean section was done were included in this study. Indications for which Caesarean section was done were studied and results were compared with similar studies in other hospitals. Results: Overall rate of caesarean section observed in this study was 43.3%. Incidence of caesarean section in primigravidae was 59.5%. Only 2.1% of the patients underwent trial of scar resulting in vaginal birth. Foetal distress was one of the most common indicatorsfor caesarean section and its detection was based on foetal cardiotocograph readings. Out of all patients taken for caesarean section due to foetal distress only 28.5% of the babies required neonatal intensive care admission. Rising trend towards caesarean section on maternal request was also seen. Conclusions: Current climate of high professional liability is detrimental to good patient care as defensive medicine provides less benefit and much harm. Practice of medicine should be safe and hassle free. For this, standard protocols should be made and followed and if practitioners are abiding with standard protocols they should be protected against litigation.